Vera. Set 8 [videorecording (DVD)] - Gay, Paul; Leon, David, 1980-; Blethyn, Brenda, 1946-; Doughty, Kenny, 1975-; Ben-Adir, Kingsley; Cleeves, Ann (BBC, 2018)
Vera Stanhope, a caustic, disheveled investigator, solves murders in Northumberland, England.